Sosialisasi Implementasi Peran Aktif Masyarakat Terhadap Kepedulian Lingkungan Laut, Keselamatan, dan Kesehatan Kerja Pada Masyarakat Pesisir - Prasetyo, Dwi; Tungga Dewi, Imelda Zahra; Cahyadi, Imam; Antarest Erland Prasetyo (Politeknik Ilmu Pelayaran Semarang, 2025)
Coastal areas play an important role in marine ecosystems as well as in the social and economic life of the community. However, environmental pollution and low awareness of occupational safety and health (OHS) are the main challenges faced by coastal communities. This community service activity aims to increase public awareness of the marine environment and implement OHS principles through socialization and training. The methods used include socialization, practical training, and mentoring and evaluation. The results of the activity showed a significant increase in public awareness of marine cleanliness, from 45% before socialization to 85% afterward. In addition, compliance in the use of personal protective equipment (PPE) increased from 30% to 70%. This activity also encourages the formation of local communities that actively maintain the cleanliness of the beach. With a community-based approach, it is hoped that coastal communities will play an increasingly active role in protecting the environment and implementing occupational safety in a sustainable manner.